Intense Red Upconversion Emission and Shape Controlled Synthesis of Gd2O3:Yb/Er Nanocrystals - Zhigao Yi; Boyun Wen; Chao Qian; Haibo Wang; Ling Rao; Hongrong Liu; Songjun Zeng (Advances in Condensed Matter Physics)
Yb/Er codoped Gd(OH)3 was synthesized firstly via a simple hydrothermal treatment of the corresponding nitrate in the presence of alkali by tuning the pH values. The Gd2O3:Yb/Er nanocrystals were obtained via sintering the corresponding hydroxides precursors. The as-prepared samples were characterized by the typical X-ray diffraction, energy-dispersive X-ray spectroscopy, transmission electron microscopy (TEM), high-resolution TEM, and spectrophotometer. The results revealed that two shapes of the as-prepared Gd2O3:Yb/Er nanocrystals can be readily tuned from lemon-like particle to rod-like structure via tuning pH values from 7 to 14. Moreover, compared with the samples prepared at pH 7, the Gd2O3:Yb/Er nanocrystals prepared at pH 14 exhibit enhanced red upconversion emission and higher upconversion luminescence intensity under the excitation of 980 nm laser.